2020
DOI: 10.1111/jsap.13270
|View full text |Cite
|
Sign up to set email alerts
|

Joint laxity in canine hip dysplasia assessed using the hip flexed not distracted ventrodorsal view

Abstract: Objectives The ventrodorsal hip extended standard view is conventionally used for radiographic screening of canine hip dysplasia. However, because the ventrodorsal hip extended standard view minimises hip joint laxity, several alternative views have been proposed. Our aim was to evaluate a new ventrodorsal hip flexed and not distracted view to assess joint laxity, by comparing it with the ventrodorsal hip extended standard and ventrodorsal hip flexed and distracted views. Materials and Methods Between April 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Although the gold standard of CHD diagnosis is radiographic examination [ 8 , 10 ], the results of this study demonstrated that ultrasonographic evaluation can be used as a screening method and diagnostic aid for CHD and that the association of both imaging methods can bring greater accuracy in disease investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the gold standard of CHD diagnosis is radiographic examination [ 8 , 10 ], the results of this study demonstrated that ultrasonographic evaluation can be used as a screening method and diagnostic aid for CHD and that the association of both imaging methods can bring greater accuracy in disease investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Radiographic examination of the hip is the gold standard for diagnosing dysplasia [ 5 , 7 , 8 ]. Numerous radiographic approaches can be employed to assist in the investigation of secondary disease [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…This view was first proposed by Schnelle [4] in an effort to reproduce the radiographic features of human being's coxo-femural dysplasia, however this positioning is not natural in the dog. B) Same dog studied with a ventro-dorsal view in which the coxo-femural joints are flexed and positioned in a more natural positioning: both the hip joints show now a severe laxity with lateral subluxation of the femural heads [13]. performed to rule out lung metastasis, it is reccomended to perform it on animals in general anestesia and during a positive ventilation [18].…”
Section: The Thoraxmentioning
confidence: 99%
“…fractures or luxations), the patient has to be sedated or anaesthetized in order to better visualize a lesion, when it is necessary to obtain a more stressed positioning, ( Fig. 2 ) [ 13 ].
Fig.
…”
Section: Radiographymentioning
confidence: 99%